A Study on the Effect of Alcoholism on the Family Members of Alcoholic Patients - Chinnusamy, Manokaran; Eugin, Priscilla Rubavathy; Janakiraman, Sathiyanarayanan (Journal of Health and Allied Sciences NU, 2021)
Introduction Alcohol use disorder is commonly known as “alcoholism” but is also known as a family disorder, not because it runs in families but because it tends to impact the family members more than just the individual. Alcoholism is one of the leading causes of marital problems, divorce, domestic violence, child abuse and neglect, and strained relationships between the partners and also between the parent and child. The per capita alcohol consumption has increased from 2.2 L (2005) to 2.7 L (2016) and is expected to increase by another 2.2 L by 2025. According to the World Health Organization, 55% of domestic violence is related to alcohol abuse by the partner. This study aims to identify the impact of alcoholism on the individual’s health as well as the family members depending on the level of alcohol dependence.Materials and Methods A cross-sectional study was conducted among patients admitted in the ward with a history of alcohol intake. AUDIT-C (Alcohol Use Disorders Identification Test–C) questionnaire was used to detect dependence and also a structured questionnaire was used to gather information regarding the financial and psychological well-being of the family from the family member accompanying the person. Other parameters of the patient were also considered such as liver function test, abdomen ultrasonography, and upper gastrointestinal endoscopy, wherever available.Results A total of 100 patients were included in the study; 59 patients were admitted due to various reasons secondary to alcohol intake. A score of >4 was suggestive of alcohol dependence: 73% (73) of the participants had a score of >4; 65% of the participants’ family members gave a positive history of impaired interpersonal relationships; 45% gave a positive history of battering; and 69% had mental health issues such as depression, lack of confidence, inferiority complex, and decreased sleep. Also, 51% (51) gave a positive history of financial contribution by the participant toward the family expenses.Conclusion The study shows that the problems of alcohol abuse have been associated with increased suffering to the family members, which contributes to a high level of interpersonal conflict, domestic violence, financial difficulties, and psychological disturbances, along with increasing the risk of developing comorbidities associated with alcohol abuse by the individual, which further adds to burden of the family.
Keywords: alcoholism; alcoholism and family relationship; impact of alcoholism